The effect of zearalenone mycotoxins at late gestation days on the development and reproductive organs - YULIA IRNIDAYANTI (Nusantara Bioscience, 2012)
Abstract. Irnidayanti Y. 2012. The effect of zearalenone mycotoxins administration at late gestation days on the development and reproductive organs of mice. Nusantara Bioscience 4: 1-5. Zearalenone was injected subcutaneously with a dose of 30 mg/kg body weight to pregnant mice on the 13 to 16 days. Control was given only sesame oil. Control and treated mice were killed on day 18 of gestation by cervical dislocation. Observations of maternal body weight, reproductive performance, external and internal malformation were conducted. Histological analysis of fetal ovaries, uterus, and testes was also done. The results revealed that administration of zearalenone to mice at late gestation was not teratogenic. Zearalenone caused a tendency that the primordial follicles and follicular cells relatively decreased in number and the number of the degenerate primordial follicle relatively increased. Effects of zearalenone on the uterus caused a significant increase in the height of lumen epithelial cells and in the thickness of the uterine wall were significant. The lamina propria and myometrium started to differentiate. In the male fetus, zearalenone caused a tendency to decrease in number of the Leydig cells.